Penapisan Fitokimia, Kadar Kurkuminoid dan Aktivitas Antibakteri Temu Hitam (Curcuma aeruginosa (Christm) Roscoe.), Temu Putih (Curcuma zedoaria Roxb.) dan Temulawak (Curcuma xanthorrhiza Roxb.) - Lia Marliani; Ika Kurnia Sukmawati; Dadang Juanda; Elmadhita Anjani; Ira Anggraeni (Universitas Muhammadiyah Purwokerto, 2021)
The content of secondary metabolites in the rhizome of the Curcuma genus such as Black turmeric (Curcuma aeruginosa Roxb.), White turmeric (Curcuma zedoaria (Christm.) Roscoe) and Java turmeric (Curcuma xanthorrhiza Roxb.) play a role in various pharmacological activities. One of them is the content of the curcuminoid compounds which have been proved to have antibacterial activity. This study aims to screen the content of secondary metabolite compounds, determine curcuminoid content and verify the antibacterial activity of the extracts of Black turmeric (Curcuma aeruginosa Roxb.), White turmeric (Curcuma zedoaria (Christm.) Roscoe) and Java turmeric (Curcuma xanthorrhiza Roxb.). Extraction was carried out by the maceration method using 95% ethanol as solvent. Phytochemical screening was tested for the content of alkaloid, polyphenols, flavonoids, quinones, tannins, saponins, and steroids/ triterpenoids compounds. Determination of curcuminoid content by UV-Vis Spectrophotometry method. The antibacterial activity test was carried out by the microdilution method against Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acne bacteria. The results of phytochemical screening showed that the three extracts contained polyphenols and flavonoids. Quinone compounds are only contained in the extract of Black turmeric and Java turmeric. Saponin compounds were only detected in Black turmeric and White turmeric extracts. Meanwhile, steroid/ triterpenoid compounds were detected in the extract of White turmeric and Java turmeric. The results of curcuminoid content determination on the three extracts showed that the Java turmeric extract had the highest content of curcuminoids (16.07 ± 0.023 mg CE/g extract). The results of the antibacterial test showed the strongest activity of the three test samples shown by Java turmeric extract with a minimum inhibitory concentration (MIC) value of 64 mg/mL against Staphylococcus aureus bacteria; 256 mg/mL against Staphylococcus epidermidis bacteria; and 32 mg/mL against the Propionibacterium acne bacteria. These results indicate that Java turmeric extract is more active against Propionibacterium acne bacteria.